Dynamic Rational Inattention and the Phillips Curve - Hassan Afrouzi; Choongryul Yang (Center for Economic Studies and Ifo Institute (CESifo), 2021)
We develop a fast, tractable, and robust method for solving the transition path of dynamic rational inattention problems in linear-quadratic-Gaussian settings. As an application of our general framework, we develop an attention-driven theory of dynamic pricing in which the Phillips curve slope is endogenous to systematic aspects of monetary policy. In our model, when the monetary authority is more committed to stabilizing nominal variables, rationally inattentive firms pay less attention to changes in their input costs, which leads to a flatter Phillips curve and more anchored inflation expectations. This effect, however, is not symmetric. A more dovish monetary policy flattens the Phillips curve in the short-run but generates a steeper Phillips curve in the long-run. In a calibrated version of our general equilibrium model, we find that our mechanism quantifies a 75% decline in the slope of the Phillips curve in the post-Volcker period, relative to the period before it.
Keywords: D83; D84; E03; E58; 330; rational inattention; dynamic information acquisition; Phillips curve